2017
DOI: 10.3389/fimmu.2017.01079
|View full text |Cite
|
Sign up to set email alerts
|

CCL5–Glutamate Cross-Talk in Astrocyte-Neuron Communication in Multiple Sclerosis

Abstract: The immune system (IS) and the central nervous system (CNS) are functionally coupled, and a large number of endogenous molecules (i.e., the chemokines for the IS and the classic neurotransmitters for the CNS) are shared in common between the two systems. These interactions are key elements for the elucidation of the pathogenesis of central inflammatory diseases. In recent years, evidence has been provided supporting the role of chemokines as modulators of central neurotransmission. It is the case of the chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 159 publications
2
41
0
Order By: Relevance
“…These findings, in addition to our data, suggest that CCL5 may be a target for therapeutic intervention in human rabies. However, CCL5 plays a role in controlling neurotransmission by modulating glutamate release at the synapses [89,90] and dysregulation of CCL5 mediated glutamatergic transmission is linked with psychiatric disorders [89][90][91][92]. In addition, CCL5 also promotes neuronal survival during injury involving toxic insults [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…These findings, in addition to our data, suggest that CCL5 may be a target for therapeutic intervention in human rabies. However, CCL5 plays a role in controlling neurotransmission by modulating glutamate release at the synapses [89,90] and dysregulation of CCL5 mediated glutamatergic transmission is linked with psychiatric disorders [89][90][91][92]. In addition, CCL5 also promotes neuronal survival during injury involving toxic insults [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of bidirectional neuron–glia communication via CKs and other cytokines, one the one hand, and neurotransmitters and neuropeptides, on the other, is central to understanding physiological functionalities and pathological distortions. Certain inflammatory CKs cause synaptic hyperexcitability by altering glutamatergic and GABAergic neurotransmission and affect neuroplasticity ( 65 ).…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%
“…[8] There is clear evidence that CCL5 and CCR5 are strongly related to many immune-mediated diseases, such as rheumatoid arthritis (RA), multiple sclerosis (MS) and graft-versus-host disease (GVHD). [9][10][11][12][13] Although previous studies have reported that CCL5 and CCR5 are upregulated in OLP, the biological effects of the CCL5-CCR5 axis on OLP T cells remains poorly understood. [14,15] In this study, we detected the expression level of the CCL5-CCR5 axis both in the peripheral blood and local OLP lesions.…”
mentioning
confidence: 99%